Effects of intensive individualized nutrition intervention on malnutrition risk and nutritional status among elderly living in agricultural settlements - Hamirudin, Aliza Haslinda; Zainudin, Norain; A. Rahman, Nor Azlina; Sidek, Suriati (Elsevier Inc, 2021)
Rationale: Malnutrition is an issue which is commonly under-recognized among community living elderly.1 This study aimed to assess the effects of intensive individualized nutrition intervention on malnutrition risk and nutritional status among community living elderly in agricultural settlements. Methods: Malnourished and at-risk elderly aged ≥60 years old were recruited into intervention (n=30) and control groups (n=30). Intervention group received intensive individualized nutrition intervention; whilst control group received dietary counselling only. Malnutrition risk, body weight, body mass index (BMI) and dietary intake were assessed at baseline and at three months follow-up. Malnutrition risk was assessed using Mini Nutritional Assessment-Short Form (MNA-SF). Repeated measure ANOVA was conducted for data analysis. Results: At three months, mean MNA-SF score for intervention group improved significantly from being in the at risk of malnutrition category (10.6±2.3) to well-nourished category (12.1±3.4) (p=0.037). Intervention group showed significantly higher improvement in term of weight gain at three months than control group (p=0.048), but no changes in BMI were detected. Energy intake significantly increased from 1623±281 kcal/day to 1643±288 kcal/day (p=0.002) in intervention group; while 1601±264 kcal/day to 1613±269 in control group. There were no statistically significant changes in nutrients intake except for carbohydrate (p=0.008), fiber (p=0.004) and calcium (p=0.009). Conclusion: Greater improvement was demonstrated using intensive individualized nutrition intervention approach after three-month among elderly living in agricultural settlements. Routine malnutrition identification with subsequent tailored nutrition intervention is therefore warranted. References: 1Hamirudin AH, Charlton K, Walton K. Outcomes related to nutrition screening in community living older adults: a systematic literature review. Archives of Gerontology and Geriatrics. 2016 Jan 1;62:9-25.